Why do students enrol for postgraduate education in China? The influence of gender and of family habitus. Issue 2 (17th February 2020) - Liu, Dan; Morgan, W. John
ABSTRACT: The article draws upon Bourdieu's concepts of habitus and cultural capital to provide an in-depth analysis of the gender differences in students' motivation for undertaking postgraduate (PG) education in Mainland China. It reports an in-depth case study comprising 381 questionnaires and 30 semi-structured interviews. The quantitative data show that students who enter PG education do so chiefly to improve employment prospects. The qualitative data, while supporting the quantitative results, show students' motives were also gender-differentiated and how they interact with students' family habitus.